2018
DOI: 10.1080/01930826.2018.1448655
|View full text |Cite
|
Sign up to set email alerts
|

Net Promoter Score as Indicator of Library Customers' Perception

Abstract: The Net Promoter Score (NPS) used in the business to measure the customers' willingness to recommend the product, service or the enterprise as a whole to their friends or colleagues, introduced by Fred Reichheld in 2003, may for its part answer to the need of libraries to find easy and non-laborious methods of assessing the customers' experience. It may be targeted either the library as a whole or some critical services that are the most relevant to the library's main goals. However, information of the using N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
1
14
0
4
Order By: Relevance
“…Students scoring their course satisfaction as 9 or 10 were classified as satisfied (c.f., promoters in NPS), students scoring 7 or 8 were classified as neutrals (c.f., passives), and students scoring their course satisfaction as 6 or below were classified as dissatisfied (c.f., detractors). The distribution of the satisfaction scores is similar to other studies assessing experienced satisfaction towards a service or a product (e.g., [40]). The majority of the students were classified as neutrals (n = 136; 46%).…”
Section: A Comparing Course Satisfaction and Willingness To Recommensupporting
confidence: 81%
See 1 more Smart Citation
“…Students scoring their course satisfaction as 9 or 10 were classified as satisfied (c.f., promoters in NPS), students scoring 7 or 8 were classified as neutrals (c.f., passives), and students scoring their course satisfaction as 6 or below were classified as dissatisfied (c.f., detractors). The distribution of the satisfaction scores is similar to other studies assessing experienced satisfaction towards a service or a product (e.g., [40]). The majority of the students were classified as neutrals (n = 136; 46%).…”
Section: A Comparing Course Satisfaction and Willingness To Recommensupporting
confidence: 81%
“…To assess the applicability of the idea of NPS in assessing course satisfaction, we make a comparative analysis of the two scales. In a similar comparison, Laitinen [40] examined the library patrons' satisfaction and willingness to recommend a library service. He found that the two evaluation metrics converge; however, there was a statistically significant difference at the highest grades.…”
Section: B Measures 1) Course Satisfactionmentioning
confidence: 99%
“…NPS is a proxy metric: in strict terms, Figure 4. The distribution of estimates on scale from 9 to 10 on the questions "how would you grade Finna" and "how likely is it that you would recommend Finna" according to Laitinen (2018) 8 LM 40,1/2 what it measures is not precisely user satisfaction, but we as the authors of this paper believe it is a very good proxy for user satisfaction. If we compare it to the number of searches, we see that whereas the number of searches does not tell us much about the user's attitude toward our service, NPS is able to measure at least one dimension of that attitude.…”
Section: Discussionmentioning
confidence: 84%
“…The group of passively satisfied, on the other hand, are more likely to be turned into promoters. Laitinen (2018) analyzed three annual Finna user surveys performed in 2014-2016 (Table II). A rating on the average 7.9 in 2014 and 8.0 in 2015 and 2016 on a scale 0-10 was found.…”
Section: Modern Services Challenge the Traditional Evaluation Methodsmentioning
confidence: 99%
“…Net Promoter Score -NPS Este indicador, ampliamente utilizado en la medición de la satisfacción de clientes (Laitinen, 2018), se calculó empleando la pregunta 9 del cuestionario en la cual se indaga el nivel de recomendación del operador actual reportado por cada usuario.…”
Section: Funnel Analysisunclassified